Propranolol for infantile haemangiomas: insights into the molecular mechanisms of action - Storch, Caroline Henrike; Höger, Peter H. (British journal of dermatology, 2010)
Infantile haemangiomas (IH) are the most common benign tumours of infancy. Although most IH are innocuous and 85-90% regress spontaneously, some may become life‐ or function‐threatening and require immediate treatment. Previous standard therapeutic options include physical measures (laser surgery, cryosurgery) and systemic corticosteroids, in severe cases also vincristine, α‐interferon or cyclophosphamide, all bearing the risk of serious side‐effects. Oral propranolol is a very recent therapeutic option for complicated IH with impressive efficacy and generally good tolerance. The effects of propranolol on IH were discovered by chance, and very little is known about its mechanisms of action in IH. Here we present a summary of current knowledge of how propranolol interferes with endothelial cells, vascular tone, angiogenesis and apoptosis. Early, intermediate and long‐term effects of propranolol on IH can be attributed to three different pharmacological targets. Early effects (brightening of the haemangioma surface within 1-3 days after start of therapy) are attributable to vasoconstriction due to decreased release of nitric oxide. Intermediate effects are due to the blocking of proangiogenic signals (vascular endothelial growth factor, basic fibroblast growth factor, matrix metalloproteinase 2/9) and result in growth arrest. Long‐term effects of propranolol are characterized by induction of apoptosis in proliferating endothelial cells, and result in tumour regression.
Gesehen am 28.08.2023